Determinants of Tax Rates in Local Capital Income Taxation: A Theoretical Model and Evidence from Germany - Thiess Buettner (Center for Economic Studies and ifo Institute (CESifo), 1999)
In a theoretical model local jurisdictions provide a public input an d a public consumption good financed by a tax on capital income. When deciding about tax rate and budget structure the jurisdictions will generally respond to each others fiscal choices irrespective of whether the policy is more oriented towards raising local income or raising public consumption. These policy differences along with differences in size will however give rise to local differences in tax rates. The theoretical implications for the distribution of tax rates are then confronted with the case of the business tax (Gewerbesteuer) in West Germany. Taking into account possible competition effects, tax rates are found to be positively related to the population size of the communities even when controlling for density. This conforms with the hyothesis t hat large jurisdictions are less concerned with a tax policy aimed at attracting mobile capital. In addition, federally mandated local welfare expenses are established as a determinant of local tax differences raising concerns about distortions induced by the German federal system.
Keywords: 330; Capital income taxation; public inputs; local public finance; spatial econometrics; business tax (Gewerbesteuer)